2019
DOI: 10.1590/0001-3765201920180528
|View full text |Cite
|
Sign up to set email alerts
|

Water retention curve to analyze soil structure changes due to liming

Abstract: Liming can influence crop growth by altering pore geometry, pore size distribution and water retention characteristics in acid soils. The aim of this work is to determine liming effects on the soil structure based on analysis of water retention data using a cubic spline adjustment function. For that, the authors investigated the effect of three lime rates (0, 15 and 20 t ha-1) on soil water retention characteristics and pore size distribution of a silty-clay "Cambissolo Háplico Alumínico" (Dystrudept) located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Therefore, in older crops, the effect of soil compaction over time leads to soil strengthening (Jensen et al, 2020). Such strengthening generates the structural restoration of the soil over time due to the rearrangement of soil particles and clay flocculation, changing the porosity and the cementing effect of the soil, increasing bulk density (Ferreira et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in older crops, the effect of soil compaction over time leads to soil strengthening (Jensen et al, 2020). Such strengthening generates the structural restoration of the soil over time due to the rearrangement of soil particles and clay flocculation, changing the porosity and the cementing effect of the soil, increasing bulk density (Ferreira et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2022) measured the water retention curves of subgrade aggregates with different clay fine particle contents, and speculated the pores of soil aggregates with different fine particle contents. Ferreira et al (2019) also used the water retention curve to analyse the soil structure changes caused by lime, and concluded that lime no-tillage reduced the macroporosity of shallow soil and expanded the pore volume of surface pores. According to the water retention curve method, the estimation of soil pores is simple and cost-effective.…”
Section: Indirect Methodsmentioning
confidence: 99%
“…Soil microporosity is linked to the water retention capacity; soils that present a higher number of micropores tend to retain more water. The micropores also improve the overall water infiltration capacity by acting as capillary conductors for the water to flow through the soil profile [17].…”
Section: Effect Of Management On the Physical Properties Of The Soilmentioning
confidence: 99%